2017
DOI: 10.1007/s12264-017-0183-5
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers for Parkinson’s Disease: Recent Advancement

Abstract: As a multi-factorial degenerative disease, Parkinson's disease (PD) leads to tremor, gait rigidity, and hypokinesia, thus hampering normal living. As this disease is usually detected in the later stages when neurons have degenerated completely, cure is on hold, ultimately leading to death due to the lack of early diagnostic techniques. Thus, biomarkers are required to detect the disease in the early stages when prevention is possible. Various biomarkers providing early diagnosis of the disease include those of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
131
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 199 publications
(137 citation statements)
references
References 112 publications
0
131
0
6
Order By: Relevance
“…As we know, the cerebellum predominantly contributes to motor coordination, precision, and accurate timing (Fine et al, 2002), and it may also be involved in some cognitive functions (Wolf et al, 2009). Anatomical atrophy in the cerebellum in PD was observed (Lotankar et al, 2017); additionally, functional changes of the cerebellum were also reported. In a prior task-evoked fMRI study, more cerebellum areas were activated, and connections within cortico-cerebellar motor regions were strengthened in PD (Gao et al, 2017) to compensate for basal ganglia deficit when a single tapping task and simple dual-task were performed (Wu et al, 2009(Wu et al, , 2011.…”
Section: Strengthened Cerebellum Synchronization Might Compensate Formentioning
confidence: 97%
“…As we know, the cerebellum predominantly contributes to motor coordination, precision, and accurate timing (Fine et al, 2002), and it may also be involved in some cognitive functions (Wolf et al, 2009). Anatomical atrophy in the cerebellum in PD was observed (Lotankar et al, 2017); additionally, functional changes of the cerebellum were also reported. In a prior task-evoked fMRI study, more cerebellum areas were activated, and connections within cortico-cerebellar motor regions were strengthened in PD (Gao et al, 2017) to compensate for basal ganglia deficit when a single tapping task and simple dual-task were performed (Wu et al, 2009(Wu et al, , 2011.…”
Section: Strengthened Cerebellum Synchronization Might Compensate Formentioning
confidence: 97%
“…Neurochemical biomarkers, such as α-Syn, have long held promise in the field of PD for improving diagnosis and are helpful in monitoring disease progression [15,16]. Among the different sources of tissue sampling, peripheral blood has raised interest in scientists, because it is abundant, easily accessible, and a well-tolerated procedure for patients.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations of the leucine-rich repeat kinase-2 (LRRK2) gene represent one of the most common genetic causes of Parkinson's disease (PD) (1). As with idiopathic PD, LRRK2 PD is associated with the progressive loss of dopaminergic neurons in the substantia nigra pars compacta that ultimately results in debilitating motor symptoms such as bradykinesia, rigidity, and tremor…”
Section: Introductionmentioning
confidence: 99%